انسداد الأمعاء الحاد الجراحي عند البالغين - حاج قاسم, فؤاد; قنجراوي, أكثم; علان, علي (Latakia University Journal -Medical Sciences Series, 2019)
تمت دراسة (252) مريضاً قبلوا في قسم الجراحة في مشفى الأسد الجامعي في اللاذقية بتشخيص اشتباه انسداد أمعاء, وذلك من بداية شهر آب 2002 ولغاية نهاية شهر آب 2009 (7 سنوات). يهدف هذا البحث إلى دراسة أسباب انسداد الأمعاء الحاد وتقويم نتائج التدبير الإسعافي. كانت نتائج البحث على النحو الآتي: معظم أسباب الانسداد المعوي (88.88%) كانت بسبب الالتصاقات (%61.11) والفتوق الإربية (%27.77). بلغت نسبة الأسباب الأخرى التي تتضمن التنشوءات – الانفتال - التضيقات – الانغلاف (%11.12) من المرضى. بلغت حساسية صورة البطن البسيطة في التشخيص (%97.67) وبلغت نوعيتها (%70.27). خضع 183 مريضاً لعمل جراحي وحوالى (46%) تطلبوا قطع أمعاء, وذلك في المجموعة المتأخرة من الانسدادات الالتصاقية مع نسبة وفيات كلية بلغت 6.3%, ونسبة مراضة كلية بلغت(%8.6). This study included (252) patients admitted and treated in the Department of Emergency at Al-Assad University Hospital in Lattakia. with a clinical diagnosis of acute intestinal obstruction from August 2002 to August 2009 inclusive. This study aims to describe the causes of acute intestinal obstruction and assess the results of emergency management. The results of the study were as follows: most causes of intestinal obstruction (nearly 88.88%) were caused by postoperative adhesions (61.11%) and strangulated external hernias (27.77%). All other causes of obstruction including neoplasia, volvolus, strictures, and intussusceptions accounted for (11.12) of the patients. The sensitivity and specificity of the plain abdominal x-rays were (97.67%) and (70.27%), respectively. (221) patients were operated upon and nearly about (46%) required bowel resections in the delayed group of patients with adhesive obstruction, with an overall mortality of 6.3% and overall morbidity of 8.6%.